(untitled) - Hatim, Basil (New York, 2012)
This new book introduces students and teachers of translation to the intricacies of the process and demands of the subject. The author shows how theoretical perspectives relate to practical pursuits in translation and interpreting studies and presents relevant research issues and their applications to teaching.
Keywords: Translating and interpreting,Biên dịch và phiên dịch; Research,Methodology,Nghiên cứu,Phương pháp